Comparison between conventional treatment processes and advanced oxidation processes in treating slaughterhouse wastewater: a review - Jen, Xen Yeoh; Md. Jamil, Siti Nurul Ain; Syukri, Fadhil; Koyama, Mitsuhiko; Mobarekeh, Mohsen Nourouzi (MDPI, 2022)
The blooming of the world’s human population and the transition of the human diet into a more westernized, high-protein diet has accelerated the production of slaughterhouse wastewater (SWW) as the number of meat processing plants (MPP) has increased in the past few decades. Conventional treatment processes (CTP) used in treating SWW, such as anaerobic processes, membrane processes, and electrocoagulation, have significant limitations, such as low treatment efficiency, tendency to foul, and high energy consumption, respectively. While advanced oxidation processes (AOPs) appear promising in replacing the former, they lack economic feasibility when used as a single process. In this paper, the limitations and disadvantages of the CTPs used in treating SWW influents are evaluated. The idea of utilising AOPs as a “complementary” step rather than a single process is also discussed. The review paper further explores the variability of different AOPs, such as Fenton, Electro-Fenton, Sono-Fenton, etc., and their respective strengths and weaknesses in counteracting the limitations of CTPs. The idea of incorporating resource recovery into wastewater treatment is also discussed towards the end of the paper as a means of generating additional revenue for the industry players to compensate for the high operation and maintenance costs of SWW treatment. The integration of a new-generation treatment process such as AOP into CTP while being able to carry out resource recovery is a future hurdle that must be overcome by scientists in order to produce a versatile, powerful, sustainable, yet financially feasible and operationally pragmatic treatment system.